FROM LOGICAL EXPRESSIVISM TO EXPRESSIVIST LOGIC: SKETCH OF A PROGRAM AND SOME IMPLEMENTATIONS1. - Brandom, Robert (Philosophical Issues, 2018)
The article focuses on philosophy of logic are the demarcation and the binding-agents tying together semantic and logical inferentialism is a distinctive philosophy of logic a logical expressivism. Topics include the expressive role that distinguishes logical vocabulary is to make explicit the inferential relations, the semantic contents of the concepts expressed by the use of ordinary, and the sense of good inference a good thing if inference does not have true premises and a false conclusion.